Penalaran Proporsional Siswa dalam Strategi Worked Example - Ibrahim, Balqis Kurnia; Amir, Mohammad Faizal (Department of Mathematics, Universitas Negeri Gorontalo, 2024)
Elementary school students need proportional reasoning inside or outside the classroom. However, students still have difficulties in using proportional reasoning. The worked example strategy has been empirically proven to facilitate students' proportional reasoning. The study aimed to analyze the effect of the implementation of the worked example strategy on students' proportional reasoning. The research method used mixed methods with a sequential explanatory design. The research was conducted in one of the elementary schools in Krembung, East Java, Indonesia. The sample technique used was random and purposive sampling. The instruments used include proportional reasoning tests and interview guidelines. Data analysis used paired-sample t-test and thematic analysis. The results showed that there was a significant influence on proportional reasoning in the implementation of the worked example strategy. The success of proportional reasoning can be seen in the aspects of changes in two quantities and proportions. The results of this study have implications for mathematics learning. Teachers can apply the worked example strategy so that students are accustomed to imitating problem-solving steps, which can then be developed into more complex solutions to solve other problems.